ANALISIS PENGARUH CITRA MEREK, KUALITAS PRODUK, KEWAJARAN HARGA DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (Studi Pada Pelanggan Produk Oriflame Semarang) - Fitriana, Diana; Sukresna, I Made (Faculty of Economics and Business Diponegoro University, 2018)
The sales volume of Oriflame Semarang fluctuated in 2016 and 2017. The increase and decrease is an indication that the buyer has not been loyal to Oriflame products. The purpose of this study to analyze the effects arising from brand image, product quality, price fairness and customer satisfaction on customer loyalty from Oriflame Semarang users. The variables used in this study is brand image, product quality and price fairness as an independent variable, customer satisfaction as an intervening variable and customer loyalty as an dependent variable.The samples in this study were 180 respondents us purposive sampling method. This study uses analytical techniques of Structural Equation Modelling (SEM) with AMOS 24.0 as the analysis instrument. The result show that brand image has not positive and significant effect on customer satisfaction, product quality has positive and significant effect on customer satisfaction, price fairness has positive and significant effect on customer satisfaction and customer satisfaction has positive and significant effect on customer loyalty.